Customer satisfaction via information and communications technology - Zainal Abidin, Wardah (2008)
This paper attempts to elucidate the importance of Information & Communications Technology (ICT) in Customer Satisfaction. It explores several effects which the ICT has in grooming a new landscape for doing business by organisations. Several ICT innovations are discussed in relations to providing good customer services by both types of organisations: brick and mortar as well as online businesses. In addition several causes, issues and solutions faced by organisations in attaining customer satisfaction are identified. A glimpse on a recent development in providing good services to UTM students will also be introduced. However the author concludes that the importance of the human factor in customer satisfaction is still core and can never be replaced by any technologies be it ICT.